Investigation of belt misalignment effects on metal pushing v-belt continuously variable transmission - Tawi, K. B. (Cranfield University, 1997)
The existence of belt misalignment in the Van Doorne metal pushing V-belt continuously variable transmission (CVT) has always been recognised by researchers and the manufacturers themselves. However, its effect has always been assumed to be negligible and search through the literature reveals no work published so far to verify this assumption. Misalignment of the belt may increase losses and the need to improve efficiency is now of paramount importance. This work is an initial effort by the author to address this area and study the geometrical behaviour of the belt misalignment theoretically. An equation to represent this geometrical behaviour has been developed and it is able to calculate the magnitude and position of the belt misalignment at different speed ratios and at different assembled zero belt misalignment speed ratios. The condition necessary to minimise the magnitude of the belt misalignment has been determined. Verification of the equation was obtained by using a solid modeller from Unigraphics Version 10.4.0 CAD package and by experimental results. Proceeding from the above, another model to predict the belt misalignment effect on the transmission efficiency has been developed based on Coulomb friction theory. The model is able to predict the transmission efficiency trends reasonably well but not its absolute values. The results from the experimental work seems to agree only partially with the developed model. The main suspect of this disagreement would probably due to the inevitable belt slip phenomena of the belt and secondly, could be due to the vibration of the transmission which needs to be addressed in future experimental work. Nevertheless, this investigation has succeeded in showing that increasing belt misalignment does have a small effect on the transmission performance which is sometimes favourable and sometimes not. The results of the experimental work on using optical instrumentation to measure belt misalignment, has illustrated the possibilities and potentials of the system to carry out the belt misalignment measurements to a reasonable accuracy.